A model for peer‐assisted learning in paediatrics. (10th September 2013) - Gandhi, Ajay; Primalani, Nishal; Raza, Sadaf; Marlais, Matko
Summary Background: Previous studies have shown peer‐assisted learning (PAL) to be an effective method of teaching, with benefits to students and tutors; however, the effect of PAL in paediatrics has not been evaluated in the literature. This study aimed to evaluate a student‐led paediatrics revision course for students preparing for examinations in medical specialties. Methods: Students in their specialties year were invited to undergo a 1‐day revision course consisting of a lecture and small group teaching, with a supplemental revision booklet. Tutors were recruited from the final‐year cohort to facilitate the teaching. Questionnaires containing Likert‐scale questions (1, strongly disagree; 5, strongly agree) were distributed before and after the course to assess its effectiveness. Results: In all, 62 per cent (87/140) of students who attended the course responded to the study. Students felt significantly more prepared for their exam after the course (mean 3.47 post‐course versus 2.16 pre‐course), and significantly more prepared to manage children in clinical practice (mean 3.49 post‐course versus 2.53 pre‐course). Students rated the course as good (4.35/5), with the small group sessions deemed to be the most useful aspect. Tutors agreed that participating had improved their teaching in general (4.0/5), their confidence (4.1/5), their clinical knowledge (3.6/5) and their oral presentation skills (3.8/5). Discussion: The results demonstrate an effective model for students and tutors in building vital skills in paediatrics and exam preparation. This reinforces the holistic positive attributes attainable from peer‐assisted learning, and such schemes should be incorporated into undergraduate medical curricula for paediatrics to increase student confidence and potentially increase recruitment to paediatrics.